Assessment Evolution: Crafting Diagnostic Tests to Empower the Independent Curriculum in English Education at MTs Negeri 5 Brebes - Hanif, Ma’mun (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Diagnostic tests are essential in the English language curriculum for Class VII at MTs Negeri 5 Brebes, especially within the framework of an independent curriculum. This research, employing a Research and Development approach and adapting the ADDIE model, aimed to explore the implementation, design, and development of these tests. Engaging 32 students, the study focused on the feasibility of diagnostic tests for 'My School Activities' material, utilizing the V Aiken formula for data analysis. The research revealed that while diagnostic tests under the independent curriculum align with previous curricula (KBK, KTSP, 2013), they uniquely emphasize cognitive and non-cognitive diagnostics. The design of these tests is detailed, starting from Phase D English learning outcomes to validation of test question instruments. Notably, the development of the diagnostic test model proved effective for use in Class VII English subjects, as evidenced by high validation results, achieving a V score of 0.81 in the range of 0.80-1.00. This comprehensive model includes aspects such as the independent curriculum structure, English language learning, differentiated learning, teaching aids, and assessment methods. The study underscores the importance of diagnostic tests in identifying individual learning needs, thus supporting differentiated learning and enhancing the overall educational experience for students in English language learning.